The effect of local power increase on neutron flux in internal parts of the VVER-1000 Mock-Up in LR-0 reactor. (November 2018) - Košt'ál, Michal; Losa, Evžen; Schulc, Martin; Šimon, Jan; Harut, David; Klupák, Vít; Czakoj, Tomáš; Juříček, Vlastimil; Matěj, Zdeněk; Cvachovec, František; Rypar, Vojtěch
Highlights: Measurement of reaction rates in reactor baffle simulator. Comparison of calculated and measured reaction rates in reactor baffle. Measurement of fast neutron spectra in reactor baffle cooling channel. Measurement of fast neutron spectra in Mock-Up core center. Abstract: The neutron flux distribution in the internal parts of a reactor is an important parameter which affects the absorbed dose, temperature, and gas production in the materials. Therefore, the knowledge of neutron flux distribution, for example in the baffle, is important for estimation of the radiation-induced swelling and activation of this internal component. The power distribution in the periphery fuel assemblies, mostly the lateral 2–3 pin rows, has considerable influence on neutron and gamma flux in the internal reactor elements. The power distribution in the core is mostly calculated by the reactor operator using diffusion codes. These data are used as an input for transport calculations, e.g., with Monte Carlo for the fluences, displacements per atoms, gamma heating and other important values for radiation damage estimation. This paper aims to compare the experimental and calculated reaction rate distribution in a mock-up of VVER-1000 (VVER-1000 Mock-Up) internals placed in the LR- 0 reactor and compares these quantities in case of a partial change of enrichment in one fuel assembly adjacent to the baffle simulator.